Madrasah Berbagi Program as Project-Based Learning for Empathy and Social Responsibility - Ramadhan, Rudi Nur; Agustiar (Ta'dib, 2025)
The rapid advancement of digital technology has shaped Generation Alpha into a cohort deeply integrated with virtual interactions, thereby posing challenges to the development of empathy and social responsibility within real-life contexts. This study aims to examine the Madrasah Berbagi Program as a Project-Based Learning (PjBL) model in fostering empathy and social concern among madrasah ibtidaiyah students. Employing a qualitative approach with a case study design, the research was conducted at an madrasah ibtidaiyah and involved 20 fifth- and sixth-grade students, the school principal, and two teachers as key informants. Data were collected through participatory observation, semi-structured interviews, and document analysis, and subsequently analyzed through data condensation, data display, and conclusion drawing and verification. Triangulation and member checking were applied to ensure the credibility of the findings. The findings indicate that the Madrasah Berbagi Program provides authentic social experiences through students’ active involvement in identifying beneficiaries, collecting basic necessities, and directly distributing aid within the surrounding community. These activities stimulated emotional engagement, enhanced social sensitivity, and demonstrated indications of students’ prosocial behavior in their daily interactions. Although the program reflects several core principles of PjBL—such as authentic context, collaboration, and the production of tangible outputs with social impact—its implementation remains partial, as it has not fully incorporated student-driven formulation of essential questions and structured reflection as integral components of the instructional design. This study concludes that the Madrasah Berbagi Program holds strong potential as a contextual PjBL model for character education in madrasah ibtidaiyah.